The effect of stereotype threat on student-athlete math performance. (September 2017) - Riciputi, Shaina; Erdal, Kristi
Abstract: Objectives: To assess whether a subtle stereotype threat of student-athletes would cause a decrease in both academic effort and performance. Design: A 2 (Male/Female) x 2 (Athlete Prime/No Athlete Prime) design was used to assess effort and performance on a math test. Method: A subtle threat manipulation was used to prime half of 60 NCAA Division III student-athletes with their athletic identity prior to taking a difficult math test. Results: Supporting the hypotheses, student-athletes who were primed with their athletic identity attempted significantly fewer problems and received lower mean math scores than those who were not primed. Contrary to hypotheses, gender did not impact effort or performance, and there was no evidence of buffering effects of priming non-athlete identities. Conclusions: The results of this experiment provide evidence for stereotype threat effects across genders and into Division III athletes, which potentially impact student-athlete academic performance. Highlights: Priming student-athlete status before a math test caused them to attempt fewer problems. Primed student-athletes received lower math test scores than those unprimed. Stereotype threat affects DIII athletes' academic performance, not just DI.